Engineer your own success : 7 key elements to creating an extraordinary engineering career - Fasano, Anthony (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
'Focusing on basic skills and tips for career enhancement, Engineer Your Own Success is a guide to improving efficiency and performance in any engineering field. It imparts valuable organization tips, communication advice, networking tactics, and practical assistance for preparing for the PE exam--every necessary skill for success. Authored by a highly renowned career coach, this book is a battle plan for climbing the rungs of any engineering ladder'--
Keywords: Engineering -- Vocational guidance